The Role of Value Internalization in Mediating the Effect of Guidance Intensity on Islamic Consumption Behavior: Evidence from Islamic Boarding-Based Higher Education - Nuradi; Zulkhaidir; Fathan Qoriba; Abdussafiq (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2026)
This study aims to analyze the effect of student training intensity on the consumption behavior of Muslim students, with internalization values ​​as a mediating variable. The study used a quantitative approach with an explanatory survey design involving 289 students living in the dormitory environment of the Institut Muslim Cendekia. Data were collected through a structured questionnaire and analyzed using linear regression and a mediation test using the Sobel test. The results of the study indicate that training intensity has a positive and significant influence on the consumption behavior of Islamic students. Furthermore, training intensity also significantly influences the internalization of values ​​in students. Internalized values ​​have been shown to have a very strong influence on Islamic consumption behavior and act as a partial mediator in the relationship between training intensity and Islamic consumption behavior. These findings suggest that the effectiveness of training programs in Islamic higher education institutions depends not only on the frequency of training activities but also on the success of students' internalization of Islamic values. This research contributes to the growing literature on Islamic consumer behavior by emphasizing the importance of internalized values ​​as a mechanism linking religious training to individual economic behavior.